Seni Islam dalam Perspektif Al Faruqi: Sebuah Komparasi - Putrie, Yulia Eka (el Harakah: Jurnal Budaya Islam, 2009)
The perspective of Islamic arts proposed by Ismail Raji al Faruqi in his book Islamic Culture Atlas can be considered as a very comprehensive perspective of esthetics and arts based on Islamic worldview. Al Faruqi’s perspective of Islamic arts includes various genres of arts, such as literature, calligraphy, ornamentation, interior design, and music. Therefore, al Faruqi’s perspective is expected to be able to use in architecture, especially Islamic architecture. Although al Faruqi classifies architecture as a part of interior design, there are some characteristics of architecture in general different from the interior design characteristics proposed by al Faruqi. Hence, further studies are needed to place al Faruqi’s perspective in the context of architecture study. That should be done in order that al Faruqi’s perspective can be understood in architecture science. Furthermore, the characteristics are hoped to become one of the parameters in esthetic dimension of architecture objects designed in Islamic framework. Therefore, al Faruqi’s perspective of Islamic arts can enrich storage area of Islamic architecture science as the implementation of Islamic worldview. Perspektif seni Islam oleh Ismail Raji al Faruqi dalam bukunya Islamic Culture Atlas dapat dianggap sebagai perspektif estetika dan kesenian yang sangat komprehensif berdasarkan pandangan dunia Islam. Perspektif Al Faruqi tentang seni Islam mencakup berbagai genre kesenian, seperti sastra, kaligrafi, ornamen, desain interior, dan musik. Oleh karena itu, perspektif al Faruqi diharapkan dapat digunakan dalam arsitektur, terutama arsitektur Islam. Meskipun al Faruqi mengklasifikasikan arsitektur sebagai bagian dari desain interior, ada beberapa karakteristik arsitektur yang secara umum berbeda dengan karakteristik desain interior yang diajukan al Faruqi. Oleh karena itu, studi lebih lanjut diperlukan untuk menempatkan perspektif al Faruqi dalam konteks studi arsitektur. Itu harus dilakukan agar perspektif al Faruqi bisa dipahami dalam ilmu arsitektur. Selanjutnya, karakteristik tersebut diharapkan bisa menjadi salah satu parameter dalam dimensi estetika objek arsitektur yang dirancang dalam kerangka syariah. Oleh karena itu, perspektif al Faruqi tentang seni Islam dapat memperkaya khazanah ilmu arsitektur Islam sebagai implementasi pandangan dunia Islam.